Phasmarhabditis bonaquaense n. sp. (Nematoda: Rhabditidae), a new slug-parasitic nematode from the Czech Republic - Nermuť, Jiří; Půža, Vladimír; Mekete, Tesfamariam; Mráček, Zdeněk (Zootaxa, 2016)
Phasmarhabditis bonaquaense n. sp. is described and illustrated from the body of Malacolimax tenellus, from the locality of České Švýcary near the village of Dobrá Voda, the Czech Republic. Females are characterized by a body length of 2349 (1878–2626) µm and a cupola shaped tail with a long hyaline hair-like tail tip. Extremely prominent papilla-like phasmids present. Males 1829 (1414–2121) µm long. Peloderan bursa with nine pairs of rays (papillae), 1/1/1/2/1/3. One non-paired apparent papilla-like structure located near the ventral appendage anterior to the cloaca. Prominent papilla-like phasmids located close to the tail tip. Small subunit (18S), ITS, and D2-D3 expansion segments of the large subunit of ribosomal DNA were used to analyze the phylogenetic relationships of sequenced species in the genus Phasmarhabditis and other closely related species. Phasmarhabditis bonaquaense n. sp. varied from other related nematodes both in morphological characterizations and phylogenetic analysis. The life cycle of the newly described species is not well known but it is probably a facultative, mollusc-parasitic nematode able to survive permanently in the saprobic phase on decaying organic matter.